Pattern + palette sourcebook 4 : a comprehensive guide to choosing the perfect color and pattern in design - Alexander, Kathie; Rayner, Harvey, 1975- (Beverly, Mass. : Rockport Publishers, 2010)
This is a new volume in Rockport's desktop library of color and pattern. The book provides professional designers with seamless geometric patterns in a variety of color palettes to address the specific design needs of designers, art directors, and students working in textile design, product design, graphic print and website design, and advertising and corporate design.
Cover -- Title -- Contents -- Introduction -- Dark Glamour -- Life Luxuries -- Color Moods -- Galaxy -- Reinventing -- Globe-trotter -- About the Authors
"Includes copyright-free vector files for all patterns."
Print version record.
eBooks on EBSCOhost
Keywords: Color in design; Color guides; Repetitive patterns (Decorative arts); Decoration and ornament -- Themes, motives; Graphic arts; Couleur en design; Couleur -- Guides; Motifs (Art décoratif); Décoration et ornement -- Thèmes, motifs; Arts graphiques; DESIGN -- History & Criticism; Color guides; Color in design; Decoration and ornament -- Themes, motives; Graphic arts; Repetitive patterns (Decorative arts)